A comparative evaluation of genetic and gradient-based algorithms applied to aerodynamic optimization - Zingg, David W.; Nemec, Marian; Pulliam, Thomas H. (European Journal of Computational Mechanics, 2008)
A genetic algorithm is compared with a gradient-based (adjoint) algorithm in the context of several aerodynamic shape optimization problems. The examples include singlepoint and multipoint optimization problems, as well as the computation of a Pareto front. The results demonstrate that both algorithms converge reliably to the same optimum. Depending on the nature of the problem, the number of design variables, and the degree of convergence, the genetic algorithm requires from 5 to 200 times as many function evaluations as the gradientbased algorithm.